Respostas a ambientes institucionais policêntricos: hierarquização de recursos para o desenvolvimento de práticas de responsabilidade social corporativa - Anjos, Silvina Maria dos (2024)
This thesis aims to understand how companies respond to polycentric pressures by developing resources and capabilities to implement Corporate Social Responsibility (CSR) practices in polycentric institutional environments. The Resource-Based View (RBV) provides an understanding of how companies' resources and capabilities can be articulated to advance sustainability-related strategies within the firm. CSR encompasses practices beyond economic interests to minimize social and environmental issues. A qualitative descriptive study was conducted through document analysis from 2005 to 2023 and open-ended interviews with company employees and partners, which were recorded, transcribed, and categorized using software. The company developed internal resources and capabilities to meet environmental, social, and governance demands. CSR practices evolved through three phases: initial development focusing on certifications and financing, international expansion with new regulations, and consolidation with a global sustainable positioning. These actions resulted in improvements in supplier traceability, reduction of deforestation, and advances in renewable energy. The conclusions indicate that the company implemented robust CSR practices in response to polycentric institutional environments, developed internal resources and capabilities to meet social, environmental, and economic demands, and achieved significant advancements in accessing global markets with sustainability and governance. The need for legitimation and pressure from multiple power centers accelerated the adoption of CSR practices. The study suggests that institutional complexity requires innovative strategies and highlights the relevance of CSR for business competitiveness. The results are likely to be relevant with managerial implications, as they show that the polycentric pressures companies are subjected to lead them to distribute these pressures across the entire value chain, influencing both suppliers and partners to mitigate impacts and ensure a more efficient and adaptive response to the demands and challenges of different centers of power and influence.